Digital Feminism in Indonesia: The Counter-Narratives to Gender Inequality on Instagram Account of Mubadalah.id - Izza Annafisatud Daniah; Yanwar Pribadi (Jurnal Penelitian, 2023)
In the last few years, many people have used cyber religion to identify new forms of religious communities and rituals. It acts as the source of religious engagement that is different, new, creative, and alienated from ‘conventional’ religions. This article aims to reveal how Mubadalah.id as an Instagram account plays a role to provide beautification of da’wa (Islamic preaching conveyed by Islamic scholars) in countering unjust interpretations of Islamic texts toward women. In particular, it is a representation of Islamic media and women’s rights that strengthens the capacity and authority of women ulama. They are carrying on perspectives that affirm the values ​​of reciprocity, equality, cooperation, and justice in marital, familial, and social relations. Mubadalah.id is a social media campaign affiliated to the Fahmina Foundation, a notable Muslim organisation that promotes gender equality in Indonesia. Using a virtual ethnography method, this article aims to understand the strategy used by this account to counter-gender inequality narratives. This article argues that Instagram can be optimized to build a moderate gender construction in countering the mainstreaming patriarchy ideas on social media by supplying alternative interpretations served in beautified contents. In addition, this account shows the representation of women ulama in Indonesian public spaces to negotiate their identity in a Muslim-majority country.